Relationship and performance: sociometric and bibliometric study of the scientific production of the graduate program in accounting at Unisinos - Morais Aires, Otávio Augusto; Zdziarski, Alaís Daiane; Westarb Cruz, June Alisson; Citadin, Michael Willian; Torres da Rocha, Daniela (REBRAE, 2016)
The relationship between the ability to relate social actors and their performance has achieved great attention recently, indicating the need for respect among various stakeholders and their environments. Accordingly, following Torres et al. (2013), this article analyzes the scientific publications of the researchers at the Graduate Program in Accounting at Vale do Rio dos Sinos University (Unisinos) from 2007 to 2012 based on their relational perspectives and performance. Based on an analysis of curriculum lattes of those surveyed, and through sociometric methods, bibliometrics, social network analysis, and other statistical approaches, the program was identified and studied. The program has 13 researchers who presented 605 scientific publications distributed among the Annals of Congress and periodicals. These publications represent a score of 1.620 in the first three years (2007-2009) and 3.260 in the second (2010-2012), and were analyzed individually (perresearcher) with indicators of the centrality of networks. A descriptive analysis was based on the performance points of the researchers and their relational perspectives, noting, as a final consideration, a predominant direct and persistent association between indicators of relationship researchers and their performance in points (Qualis score).